Application of NeuroTrace staining in the fresh frozen brain samples to laser microdissection combined with quantitative RT-PCR analysis - Benner, Seico (BMC Res Notes, 2015)
BACKGROUND: The heterogeneity of the brain requires appropriate molecular biological approaches to account for its morphological complexity. Laser-assisted microdissection followed by transcript profiling by quantitative determination has been reported to be an optimal methodology. Nevertheless, not all brain regions can be identified easily without staining, restricting the accuracy and efficiency in sampling. The aim of the present study was to validate whether fixation and staining treatments are suitable for quantitative transcript expression analysis in laser microdissection (LMD) samples. Quantitative RT-PCR was used to determine the absolute transcript expression levels and profiles of samples obtained from the hippocampal dentate gyrus from fresh frozen mice brain sections that had been fixed with ethanol and stained with NeuroTrace. The results were compared with those obtained from unfixed and unstained samples. RESULTS: We found that the quantitative relationship of transcript expression levels between various housekeeping genes and immediate early genes was preserved, although the preparation compromised the yield of the transcripts. In addition, histological and molecular integrities of the fixed and stained specimens were preserved for at least a week at room temperature. Based on the lobe specific profiles of transcripts in the anterior and posterior lobes of the pituitary, we confirmed that no cross-contamination on transcription expressions occurred as a result of the fixation and staining. CONCLUSIONS: We have provided detailed information of the procedures on ethanol fixation followed by NeuroTrace staining on the absolute quantitative RT-PCR analysis using microdissected fresh frozen mouse brain tissues. The present study demonstrated that quantitative transcript expression analysis can be conducted reliably on stained tissues. This method is suitable for applications in basic and clinical studies on particular transcript expressions in various regions of the brain. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-015-1222-9) contains supplementary material, which is available to authorized users.